Pycnodysostosis- a rare disorder with distinctive craniofacial dysmorphia. A case report - Anka Sharma; Anirudh Upmanyu; Amit R. Parate; Vikrant O. Kasat (Elsevier, 2021)
Pycnodysostosis is a rare autosomal recessive condition caused by the mutation of CTSK gene. CTSK regulates the activity of Cathepsin K which is responsible for osteoclast-mediated bone resorption. This mutation causes the bones to become dense, sclerotic, brittle, and thus, prone to fracture. Affected individuals have normal cognitive development and life expectancy, however, the quality of life depends on the early diagnosis of the condition. The patient presents with striking clinical (short stature, brachydactyly) and radiological (frontal and parieto-occipital bossing, open sutures, and fontanelles, acro-osteolysis of terminal phalanges) features making the diagnosis clinico-radiographic. In atypical or mild cases with overlapping features, gene mapping is advocated. A plethora of dental anomalies and characteristic craniofacial dysmorphia puts the dentist in a position to diagnose such a case.